2019
DOI: 10.1088/1748-9326/ab424a
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of long-term infrastructure decisions—the case of self-healing roads and their CO2 emissions

Abstract: What could be the reduction in greenhouse gas emissions if the conventional way of maintaining roads is changed?Emissions of greenhouse gases must be reduced if global warming is to be avoided, and urgent political and technological decisions should be taken. However, there is a lock-in in built infrastructures that is limiting the rate at which emissions can be reduced. Self-healing asphalt is a new type of technology that will reduce the need for fossil fuels over the lifetime of a road pavement, at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Hybrid LCAs are used for carbon footprint studies of products, companies or sectors by extending IO tables with physical environmental satellites (Liu et al 2012, Norwood and Kammen 2012, Rodríguez-Alloza et al 2019, Heihsel et al 2019b. Numerous sustainability studies expand the focus on further economic and social indicators, the so-called TBL (Elkington 1998, Foran et al 2005, Onat et al 2014, Malik et al 2016, Hadjikakou et al 2019.…”
Section: Methods and Datamentioning
confidence: 99%
“…Hybrid LCAs are used for carbon footprint studies of products, companies or sectors by extending IO tables with physical environmental satellites (Liu et al 2012, Norwood and Kammen 2012, Rodríguez-Alloza et al 2019, Heihsel et al 2019b. Numerous sustainability studies expand the focus on further economic and social indicators, the so-called TBL (Elkington 1998, Foran et al 2005, Onat et al 2014, Malik et al 2016, Hadjikakou et al 2019.…”
Section: Methods and Datamentioning
confidence: 99%
“…A joint analysis period was then chosen to correspond to the longest service life (e.g. Chen Noda et al 2016;Huang et al 2018;Rodríguez-Alloza et al 2019;Cadenazzi et al 2019Cadenazzi et al , 2020Landi et al 2020), the shortest service life (Stripple et al 2016;Cantisani et al 2018), or a common denominator between the service lives (Liu et al 2020). Others used an analysis period in which each alternative is rehabilitated at least once (Puccini et al 2019) or that includes a complete life cycle of all alternatives (Batouli et al 2017).…”
Section: Comparing Alternatives With Different Intended Service Livesmentioning
confidence: 99%
“…Papers that considered the end-of-life of alternatives also accounted for reconstruction of the alternative with the shortest service life (e.g. Noda et al 2016;Stripple et al 2016;Simões et al 2017;Al-Ayish et al 2018;Rodríguez-Alloza et al 2019;Cadenazzi et al 2019Cadenazzi et al , 2020Rempelos et al 2020).…”
Section: Comparing Alternatives With Different Intended Service Livesmentioning
confidence: 99%
“…This material can repair damage (through a hybrid input-output system) caused by natural disasters or road accidents. They concluded that self-healable roads may decrease emissions by 16 percent and decrease costs by 32 percent compared with a conventional road over the service life [85].…”
Section: Prospectsmentioning
confidence: 99%